Wnt targets genes are not differentially expressed in desmoid tumors bearing different activating β-catenin mutations. Issue 4 (April 2019) - Timbergen, Milea J.M.; Janssen, Matthijs L.; Verhoef, Cornelis; Grünhagen, Dirk J.; Chibon, Frederic; Smid, Marcel; Sleijfer, Stefan; Wiemer, Erik A.C.
Abstract: Introduction: Sporadic desmoid-type fibromatosis (DTF) is a rare soft tissue tumor of mesenchymal origin. It is characterized by local invasive growth and unpredictable growth behavior. Three distinct mutations involving the CTNNB1 (β-catenin) gene have been identified in the vast majority of DTF tumors, which cause activation of the Wnt signaling pathway and impact prognosis. This study examines whether the different CTNNB1 mutants (T41A, S45F) occurring in DTF tumors differentially affect Wnt signaling activity, which might explain the different disease course between DTF patients harboring different CTNNB1 mutations. Materials and methods: Real-time polymerase chain reaction (RT-PCR) on 61 formalin fixed paraffin embedded DTF samples with known CTNNB1 status was used to measure the relative mRNA expression level of Wnt target genes AXIN2, DKK1 and CCND1 . Additionally, publicly available mRNA expression data retrieved from the Gene Expression Omnibus of 128 DTF samples were used for an unsupervised cluster analyses based on the expression of a selection of Wnt targets. Results: No statistically significant difference in relative expression levels of Wnt target genes AXIN2, DKK1 and CCND1 was identified between either CTNNB1 wild-type, S45F or T41A mutated DTF samples. Moreover, the hierarchical cluster analyses using selected Wnt targets did not discriminate between different CTNNB1 mutation types. Conclusions: No differences in the expression levels of Wnt target genes were observed between the different CTNNB1 mutation types in DTF tumors. Further studies are needed to decipher the mechanism accounting for the diverse disease courses between DTF patients with different CTNNB1 variants.